UNIVERSAL PRIMERS FOR DETECTION OF COMMON BACTERIAL PATHOGENS CAUSING PROSTHETIC JOINT INFECTION - Sauer, Pavel; Gallo, Jiri; Kesselova, Michaela; Kolar, Milan; Koukalova, Dagmar (Biomedical papers, 2005)
The diagnosis of low grade prosthetic joint infection is difficult and time consuming. Nested-PCR for universal bacterial DNA segments detection of ``orthopaedic'' bacteria was tested in a laboratory setting. This method is based on amplification of the 16S bacterial ribosomal RNA coding sequences. 11 species of the most frequent bacterial pathogens (Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pyogenes, Streptococcus agalactiae, Enterococcus faecium, Enterococcus faecalis, Klebsiella pneumoniae, Escherichia coli, Proteus mirabilis, Pseudomonas aeruginosa, Serratia marcescens) involved in prosthetic joint infections were studied. All could be detected rapidly and sensitively by this method.
Keywords: Ribosomal RNA/Bacterial detection/Universal primer/Nested-PCR/Prosthetic joint infection/Diagnostics